MAKNA IMPERATIF KALIMAT DEKLARATIF DAN INTEROGATIF PADA TEKS TERJEMAHAN AL QUR’AN SURAH AL-BAQARAH - Andi Puspita Sari; Rahmat Rahmat (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Imperative Meanings of Declarative and Interrogative Sentences in Translation Texts of the Qur'an Surah Al-Baqarah. This study aims to describe the imperative meaning in declarative and interrogative sentences contained in the translation text of the Al-Qur'an surah Al Baqarah. This type of research is descriptive and qualitative. The object of research is the imperative meaning in declarative and interrogative sentences contained in the translation text of the Al-Qur'an surah Al Baqarah. The data collection technique in this study is observation and note taking. The results of this study show that there are 10 translation texts in Al Quran Surah Al Baqarah that include imperative meanings in declarative sentences, and there are 3 translation texts that include imperative meanings in interrogative sentences. The conclusions obtained in this study are imperative meanings in declarative sentences found in the translation text of the Al Quran surah Al Baqarah. Researchers managed to find imperative meanings of prohibitions, orders, recommendations, and permissions. As for the imperative meaning in interrogative sentences contained in the translation text of the Al Quran surah Al Baqarah, namely the imperative meaning of orders, commands, and prohibitions.